Long-term results of a prospective phase II trial of medically inoperable stage I NSCLC treated with SBRT – the Nordic experience. (September 2015) - Lindberg, Karin; Nyman, Jan; Riesenfeld Källskog, Vendela; Hoyer, Morten; Lund, Jo Å.; Lax, Ingmar; Wersäll, Peter; Karlsson, Kristin; Friesland, Signe; Lewensohn, Rolf
Abstract Background. Presentation of long term results of a phase II multicenter Nordic trial of medically inoperable stage I non-small cell lung cancer (NSCLC) treated with stereotactic body radiotherapy (SBRT). Material and methods. We report the extended outcome, focusing on long-term effects, of a prospective cohort of 57 evaluable patients with peripherally located T1N0M0 (72%) and T2N0M0 (28%) NSCLC, treated with SBRT 15 Gy × 3, prescribed to the 67% isodose line encompassing the PTV. The patients were inoperable due to chronic obstructive pulmonary disease (65%), cardiovascular disease (25%) or other illnesses (3%) or refused surgery (7%). Median Karnofsky score pre-treatment was 80% (70–100%). Late effects were defined as occurring > 36 months. Results. Thirty-eight patients (67%) were relapse free during their entire follow-up. Local control rate at four and five years were 79% (CI 95% 64–95%) and local relapses occurred at 10–76 months post-treatment. Seven local failures were noted, four occurring ≤ 36 months (all T2a-tumors; two isolated and two in combination with out-of-field relapses) and three occurring > 36 months (T1b-tumors n = 3). Thirteen patients had out-of-field failure only as first presentation of recurrence. Overall survival rate and lung cancer-specific survival rate at five years were 30% and 74%, respectively. Toxicity throughout the entire observation period was acceptable without any grade 5 toxicities. Seventeen grade 3–4 toxicities were noted, three presenting > 36 months (rib fracture, dyspnea and ventricle tachycardia). Median follow-up was 41.5 months (3.4–113.0) for the entire cohort and 59.3 months (36.4–113.0) for the 34 patients (60%) with a follow-up of > 36 months. Conclusion. Throughout the observation period local control was excellent and toxicity limited with no increase in late presenting local relapses or late treatment-related morbidity. This further supports SBRT as an efficient local treatment modality even in a medically impaired patient cohort.